Global, regional and national burdens of otitis media in children and adolescents from 1990 to 2021 and its predictions to 2040 - Chen, Ru; Deng, Jing; Sun, Yao; Sun, Dongxun; Lu, Haibin; Jiao, Xinfang; Zhu, Feng; Lu, Liangjie; Sima, Guoqi (Frontiers in Public Health, 2025)
BackgroundOtitis media (OM), including acute OM, chronic OM, and OM with effusion, is associated with varying degrees of hearing impairment. Children and adolescents (CAAs) are particularly vulnerable to OM. However, epidemiological data on OM in CAAs is relatively scarce. This study investigates the global, regional, and national burden of OM in CAAs from 1990 to 2021, with projections extending to 2040.MethodsData were extracted from Global Burden of Diseases (GBD) 2021 on incidence, prevalence, deaths and disability-adjusted life years (DALYs). Trends were evaluated using the metric of estimated annual percentage change (EAPC). Subgroup analyses were conducted according to socio-demographic index (SDI), and age. Additionally, projections were estimated for 2040 using the Nordpred model.ResultsGlobally, the rates with their 95% uncertainty intervals (UI) in 2021 were 12473.66 (7287.91–19931.88) for incidence, 2438.73 (1918.03–3055.21) for prevalence, 0.0095 (0.0022–0.0320) for deaths, and 49.33 (27.68–78.84) for DALYs. From 1990 to 2021, the EAPC and its 95% UI of incidence rate increased by 0.13 (0.11–0.16), while EAPC of deaths −3.79 (−4.07 to −3.52), prevalence −0.08 (−0.09 to −0.07), and DALYs −0.2 (−0.23 to −0.17) decreased. The aforementioned indicators are negatively correlated with the SDI. Regionally, both mortality rates and DALYs significantly decrease with increasing SDI. Sub-Saharan Africa and South Asia have high levels of incidence and prevalence. At the national level, countries with a high burden of OM are primarily concentrated in Sub-Saharan Africa and South Asia. For example: Pakistan, India, Ethiopia, Kenya, Nepal, Bangladesh, Somalia, South Sudan, Mozambique, Burundi, and Madagascar. From 2022 to 2040, the incidence rate, prevalence, and DALYs of OM are expected to show a downward trend. However, the mortality rate may slightly increase.ConclusionFrom 1990 to 2021, there has been some progress in the management of OM. However, the incidence in CAAs has increased. Epidemiological data vary across different regions and countries, with regions and countries with lower SDI typically experiencing a heavier burden. It is necessary to implement dynamic monitoring of OM in CAAs and develop strategies to mitigate the future burden of this disease.